MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI PENGGUNAAN SMARTBOARD DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SDN 07 MUDIAK LAWE KECAMATAN SUNGAI PAGU KABUPATEN SOLOK SELATAN - Arum Edwi Jandri; Deka Anggara; Mulia Nopemberi; Nabila Ramadhani; Nita Ardila; Zahara Putri Yuni; Ade Marlia (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the effectiveness of using a Smartboard in increasing students' enthusiasm for learning in the Pancasila Education subject in grade V of SDN 07 Mudiak Lawe, Sungai Pagu District, South Solok Regency. From initial observations, it was seen that students' enthusiasm for learning tended to be low, as seen from their inactive attitudes, little interaction, and easily distracted when teachers used less diverse learning methods. To address this, a Smartboard was proposed as an innovative solution. This tool is an interactive whiteboard that uses multimedia and audiovisual technology, so it can combine teaching materials with images, videos, and animations to make learning more interesting and diverse. The method used in this study was the correlation method, namely a quantitative method that studies the relationship between the use of Smartboard interactive features and the level of student enthusiasm for learning. The results showed that the use of Smartboard in learning was proven to be able to increase student enthusiasm for learning. After implementing the Smartboard, students appeared more active and enthusiastic during the learning process, so that their enthusiasm for learning increased and reduced boredom. The implementation of Smartboard involves game-based learning methods such as Duck Race Games and Wordwall, which successfully trigger students' curiosity, focus, and enthusiasm, and encourage them to actively participate in answering questions and interacting in class.